Analisis Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Puskesmas Alor Kecilkecamatan Alor Barat Lautkabupaten Alor - Sri Wuandari Teibang (Jurnal Ilmiah Wahana Pendidikan, 2023)
Patient satisfaction is a feeling of pleasure, individual satisfaction due to the fulfillment of expectations or desires in receiving health services, patient satisfaction is directly related to the quality of hospital/Puskesmas services by knowing the level of patient satisfaction, Hospital/Puskesmas management can improve service quality, which in research This is influenced by several factors, namely physical evidence, reliability, responsiveness, assurance, and empathy. In this study, researchers used several previous studies that had been carried out by other people with the same variables and several indicators proposed by experts. This research uses quantitative research methods. The population in this study were 25 community members who had used services at the Alor Kecil Health Center, Alor Barat Laut District, Alor Regency. Instrument trials were carried out with validity and reliability tests and several classical assumption tests used, namely normality, heteroscedasticity, multicollinearity and linearity. Meanwhile, to determine the effect of the independent variables on the dependent variable, multiple linear regression analysis was used, using the t test to determine the effect partially and the F test to determine the effect simultaneously. The data was taken by distributing questionnaires to the people of Alor Regency who had used the services of the Alor Kecil Health Center, Northwest Alor District, Alor Regency. Data analysis was performed using SPSS 22.00. From the processed results of the questionnaire data it is said to be valid because the person correlation value per statement item for each variable is more than the validity limit, which is 0.3 and is declared reliable because the Cronbach's alpha value for each variable is more than the reliability limit, which is 0.6. The research data passed the classical assumption test because they were normally distributed, there was no heteroscedasticity, there were no symptoms of multicollinearity and there was a linear relationship with the value of each test being greater than the alpha value of 0.5. Based on the research results obtained, it was concluded that the variables of physical evidence, reliability, responsiveness, assurance, and empathy partially and simultaneously have a significant effect on patient satisfaction at the Alor Kecil Health Center, Alor Barat Laut District, Alor Regency. This is indicated by the significance value of the t test or partial test on the physical evidence variable of 0.016 or 1.6%, the significance value of the t test on the reliability variable is 0.040 or 4.%, the significance value of the t test on the responsiveness variable is 0.032 or 3.2%, the significance of the t test on the guarantee variable is 0.028 or 2.8%, the significance value on the empathy variable is 0.000 or 0% and simultaneously the variables of physical evidence, reliability, responsiveness, assurance, and empathy together have a significant effect on patient satisfaction with scores F test significance of 0.000 or 0.0%.